2015
DOI: 10.3390/ijerph121214985
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption Potential of Bacillus salmalaya Strain 139SI for Removal of Cr(VI) from Aqueous Solution

Abstract: The present study investigated the biosorption capacity of live and dead cells of a novel Bacillus strain for chromium. The optimum biosorption condition was evaluated in various analytical parameters, including initial concentration of chromium, pH, and contact time. The Langmuir isotherm model showed an enhanced fit to the equilibrium data. Live and dead biomasses followed the monolayer biosorption of the active surface sites. The maximum biosorption capacity was 20.35 mg/g at 25 °C, with pH 3 and contact ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Biosorption rate increased during the first 60 minutes and slowed down after 90 minutes due to reaching the equilibrium phase. Biosorption rate might be depended on initial metal ion concentration as reported by others [44]. Adsorption isotherm models suggested by Freundlich and Langmuir were found suitable for describing the short-term biosorption of Cr(VI) in this study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Biosorption rate increased during the first 60 minutes and slowed down after 90 minutes due to reaching the equilibrium phase. Biosorption rate might be depended on initial metal ion concentration as reported by others [44]. Adsorption isotherm models suggested by Freundlich and Langmuir were found suitable for describing the short-term biosorption of Cr(VI) in this study.…”
Section: Discussionsupporting
confidence: 73%
“…TEM18 [43]. This might be due to the increase in the competition for the close-fitted binding sites amount on the surface of biosorbents [44]; which indicates the properties of biosorbents (e.g., functional groups, surface area, etc.) and the properties of metal sorbates (e.g., atomic weight, ionic size, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the kinetic model adjustment result indicated the applicability of the pseudo-second-order kinetic model to describe the adsorption of MB onto SCB for the experimental data provides a better fit. Based on the assumption of the successful fitting with the pseudo-second order kinetic model, it can be suggested that chemisorption was the rate-controlling step of adsorption speed control involving valence forces by sharing or exchanging electrons between MB and SCB [21].…”
Section: Kinetics Adsorption Experimentsmentioning
confidence: 99%
“…Before biosorption the cells were thin, long and rod-shaped. After biosorption with chromium ions, the cells appeared to be plump and spongy [43]. Earlier, the deposition of Fe (II) ions was observed on the surface of lactic acid bacteria [44].…”
Section: Sem-edx Analysismentioning
confidence: 99%